Faktor-Faktor yang Mempengaruhi Pemilihan Karier Mahasiswa Akuntansi sebagai Seorang Akuntan atau Non Akuntan - Romandhon; Laelatul Fatikha (Mulia Pratama, 2022)
This study aims to examine the effect of financial rewards, work environment, professional recognition, professional training, social values, and gender roles on accounting students' career choices as accountants or non- accountants. The population in this study were accounting students at the Wonosobo Al-Qur'an Science University. The sampling technique in this study used purposive sampling method. The sample in this study were accounting students at the Al-Qur'an Science University class of 2017 and class of 2018. The respondents who were selected as samples in this study were 112 respondents. Data collection techniques by distributing online questionnaires to accounting students at the Wonosobo Al-Qur'an Science University. Data analysis using the help of IBM SPSS Statistics v.25 application. The results show that financial rewards, work environment, professional recognition, professional training, social values, and gender roles have a positive effect on career choices for accounting students as accountants or non-accountants.